Oil and commodities drive the world business cycle: A long-commodity-cycle model of the world economy over a century and a half - Vo Phuong Mai Le; David Meenagh; Patrick Minford (Cardiff University, Cardiff Business School, 2018)
This paper explores the world business cycle using unfiltered data from 1870 and looks for a theory that could account for the long wave commodity cycle in the world economy. We build a simple DSGE model that includes a long time-to-build constraint in the commodity sector. We find that this model can produce long cycles in output and commodity prices as introduced by Kontradieff (1925) and Schumpeter (1935). Our findings show that these long business cycles are produced by the long gestation of commodity capacity which causes very large swings in commodity prices.
Keywords: E10; E32; E52; 330; Longwaves; commodities; DSGE model; Indirect Inference